Performance, Movement, Posture, and Perceived Discomfort in Active vs. Static Seating. (November 2019) - Faulk, Jeremy D.; McKee, Cameron C.; Bazille, Heather; Brigham, Michael; Daniel, Jasmine; Jaffe, Julia G.; Lee, JeeEun; Sabinson, Elena; Zhou, Yaoyi; Zhu, Yige; jin Chung2, Yoo; Hedge, Alan
Active seating designs may enable users to move more frequently, thereby decreasing physiological risks associated with a sedentary lifestyle. In this preliminary study, two active seating designs (QOR360, Ariel; QOR360, Newton) were compared to a static chair (Herman Miller, Aeron) to understand how active vs. static seating may affect task performance, movement, posture, and perceived discomfort. This within-subjects experiment involved n = 11 student participants who sat upon each of the three chairs for 20 minutes while performing a series of computer-based tasks. Participants showed increased trunk movement while also reporting higher levels of perceived discomfort in the two active chair conditions. There was no significant difference in either posture or fine motor task performance between the active and static conditions. Future research may benefit from additional physiological measurements along with a wider variety of tasks that require seated users to make postural adjustments.